Նորահայտ ձեռագիր Վերին Նորավանքից - Բարսեղյան, Լուսինե (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Верин (Верхний) Нораванк был образовательным учреждением Орбельских князей, выдающимся центром письменности, основанным в конце XIII века одним из основоположников Гладзорского университета – архимандритом Давидом. Сохранились десять рукописей, переписанных и иллюстрированных в течении 1312—1495 гг. в Верин Нораванке. Их число увеличивается неизвест- ным среди исследователей Евангелием, которое хранится в Национальной би- блиотеке Конгресса США (Отдел Ближнего Востока, BS95.5.V47). Книга была приобретена в 2008 г. Она написана писцом Григором в 1487 г. Заказали рукопись Хтрше и Гоар для их сына Луки. Художественное оформление рукописи в простом стиле. Книга имеет обширный колофон, в котором прослеживается история Евангелия. В памятной записи рукописи Верин Нораванк упоминается как «небесный и знаменитый священный завет». Технический анализ иллюстраций в Библиотеке Конгресса выявил, что художник рукописи использовал несколько необычные и редкие пигменты, что позволяет говорить об истинном мастерстве художника, а также о влиянии ближневосточных и местных техник изготовления керамических изделий и текстиля. Статья содержит описание рукописи, в ней также полностью процитированы памятные записи. Verin (Upper) Noravank was an educational institution and a prominent writing center of the Orbelian Principality. Archimandrite David, who also is known as a co-founder of the University of Gladzor, founded it at the end of the 13th century. During the period from the early 14th century to late 15th century (1312—1495), ten manuscripts were copied and illustrated at Verin Noravank, which have been preserved until today. The existing collection has been supplemented with a new Gospel currently kept at the USA National Library of Congress (Middle East Division, BS95.5.V47), which acquired it in 2008. It was written by scribe Grigor in 1487. According to the study, Khtrshe and Gohar ordered the manuscript for their son Luke. The decoration of the manuscript is artistic, but has a simple style. The colophon is extensive: it traces the history of the Gospel. In the colophon of the manuscript, Verin Noravank was mentioned as the “heavenly and famous holy covenant”. Technical research of illustrations in the Congress Library has produced some exciting results, including identification of unusual and rare pigments, which suggests ingenuity on the part of the artist, as well as the influence of Middle Eastern and indigenous ceramics and textile technologies. The article provides a manuscript description, as well as completely cites the colophons.
Keywords: Հայոց եկեղեցի